Jolly green MOF: confinement and photoactivation of photosystem I in a metal–organic framework. Issue 1 (23rd October 2018) - Bennett, Tyler H.; Vaughn, Michael D.; Davari, Seyyed Ali; Park, Kiman; Mukherjee, Dibyendu; Khomami, Bamin
Abstract : Photosystem I (PSI) is a ∼1000 kDa transmembrane protein that enables photoactivated charge separation with ∼1 V driving potential and ∼100% quantum efficiency during the photosynthetic process. Abstract : Photosystem I (PSI) is a ∼1000 kDa transmembrane protein that enables photoactivated charge separation with ∼1 V driving potential and ∼100% quantum efficiency during the photosynthetic process. Although such properties make PSI a potential candidate for integration into bio-hybrid solar energy harvesting devices, the grand challenge in orchestrating such integration rests on rationally designed 3D architectures that can organize and stabilize PSI in the myriad of harsh conditions in which it needs to function. The current study investigates the optical response and photoactive properties of PSI encapsulated in a highly stable nanoporous metal–organic framework (ZIF-8), denoted here as PSI@ZIF-8. The ZIF-8 framework provides a unique scaffold with a robust confining environment for PSI while protecting its precisely coordinated chlorophyll networks from denaturing agents. Significant blue shifts in the fluorescence emissions from UV-vis measurements reveal the successful confinement of PSI in ZIF-8. Pump–probe spectroscopy confirms the photoactivity of the PSI@ZIF-8 composites by revealing the successful internal charge separation and external charge transfer of P700 + and FB − even after exposure to denaturing agents and organic solvents. This work provides greater fundamental understanding of confinement effects on pigment networks, while significantly broadening the potential working environments for PSI-integrated bio-hybrid materials.